Classroom input to accelerate feature reassembly of English generics. Issue 2 (9th October 2018) - Abumelha, Mary
Abstract : This is an experimental study on the effect of explicit and implicit classroom input on the acquisition of English generics by L1-Najdi Arabic speakers. Following a feature-based contrastive analysis, acquisition difficulties are predicted with indefinite singular and bare plural contexts. The experiment included fifty-four students divided into two experimental groups and one uninstructed control group. One experimental group received implicit input by using genre analysis of texts reinforced with generic noun phrases (NPs), and the other group received explicit grammatical 'focus on form' on generics. Two instruments were used: a forced choice task and a sentence repetition task conducted as pre-tests, post-tests and delayed post-tests. The results showed a significant increase in the total scores of both experimental groups, but a long-term effect was only found with the explicit group. The forced choice task showed significant improvement in the explicit group's accuracy on generic indefinite singular and bare plural contexts and long-term improvement on the bare plural. The explicit group's results on the repetition task show temporary improvement in the generic indefinite singular post-test. In general, the results suggest that explicit input is more effective than implicit input. Implications on acquisition difficulties and instruction are discussed.